Rancangan Renovasi Interior Panti Asuhan untuk Yayasan Arrahman, Yogyakarta: Orphanage Interior Design Renovation for the Arrahman Foundation, Yogyakarta - Tessa Eka Darmayanti; I Nyoman Natanael; Dewi Isma Aryani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
An orphanage is a foster home for individuals who do not have parents and need a place to live and foster parents. The Arrahman Foundation, based in Magelang as a social institution, has carried out various social activities and managed orphanages in Central Java. Community service activities began with the hope of the Arrahman Foundation to increase the number of foster children at the Yogyakarta branch of the orphanage. The orphanage's interior planning needs to support this hope, which can accommodate more foster children by always considering functional and aesthetic aspects. Therefore, the interior redesign is carried out as a Community Service activity to renovate the existing orphanage space with a new one with a more attractive and accommodating design. This interior redesign activity also provides direction and advice regarding interior design to the foundation's management so that it can be applied to other room renovations. The executor of the service, which was carried out online, involved three lecturers from the Faculty of Arts and Design, Maranatha Christian University, Bandung, with whom two Interior Design Undergraduate Program students assisted. The community service activities result in a better understanding of interior design, especially for institutions, and insight into ​​redesigning a building or room.